A comparative analysis of the content of parental responsibilities and rights during the "sex alteration decisionmaking process" of intersexed infants - Thompson, Sabrina (Stellenbosch : Stellenbosch University, 2021)
Thesis (LLM)--Stellenbosch University, 2021.